2016
DOI: 10.1371/journal.pone.0167187
|View full text |Cite
|
Sign up to set email alerts
|

The Central Role of KNG1 Gene as a Genetic Determinant of Coagulation Pathway-Related Traits: Exploring Metaphenotypes

Abstract: Traditional genetic studies of single traits may be unable to detect the pleiotropic effects involved in complex diseases. To detect the correlation that exists between several phenotypes involved in the same biological process, we introduce an original methodology to analyze sets of correlated phenotypes involved in the coagulation cascade in genome-wide association studies. The methodology consists of a two-stage process. First, we define new phenotypic meta-variables (linear combinations of the original phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…This association could be explained by a putative regulation of KNG1 also on FVIII, which would imply an effect of KNG1 on the common pathway of coagulation. Associations of KNG1 with the entire coagulation cascade, and not just the intrinsic pathway, have been proposed by others 72. The significant colocalization analysis between VTE and FVIII in this locus aligns with previous evidence and suggests that rs710446 affects the regulation of both phenotypes along with other related hemostatic phenotypes.…”
Section: Discussionsupporting
confidence: 87%
“…This association could be explained by a putative regulation of KNG1 also on FVIII, which would imply an effect of KNG1 on the common pathway of coagulation. Associations of KNG1 with the entire coagulation cascade, and not just the intrinsic pathway, have been proposed by others 72. The significant colocalization analysis between VTE and FVIII in this locus aligns with previous evidence and suggests that rs710446 affects the regulation of both phenotypes along with other related hemostatic phenotypes.…”
Section: Discussionsupporting
confidence: 87%
“…The essential component of the coagulation pathway KNG1 [75], was consistently reduced in AD CSF in 3 independent proteomic studies. KNG1 is particularly attractive for further investigation since a direct relation between KNG1 and AD has not yet been reported.…”
Section: Proteins Consistently Reduced In Ad Csfmentioning
confidence: 94%
“…However, some studies have indicated that they may interact with each other in the coagulation pathway. KNG1 and HRG have similar structures and are adjacent to each other on chromosome 3, which suggests that these proteins may exhibit similar functions ( 24 , 25 ). HRG deficiency is associated with enhanced blood coagulation, which indicates that decreased KNG1 is a potential cofactor to enhance coagulation ( 26 ).…”
Section: Discussionmentioning
confidence: 98%